Nodules and masses are associated with malignant pleural effusion in dogs and cats but many other intrathoracic CT features are poor predictors of the effusion type. Issue 3 (17th December 2018) - Reetz, Jennifer A.; Suran, Jantra N.; Zwingenberger, Allison L.; Stefanovski, Darko
Abstract: Thoracic CT may be used in the workup of patients with pleural effusion. In humans, certain pleural features on CT aid in diagnosing an underlying cause for pleural effusion, whereas this is not well studied in veterinary medicine. This retrospective cross‐sectional analytical study assessed pleural and other intrathoracic abnormalities on CT in dogs and cats with pleural effusion and explored potential discriminatory features between effusion types. Eighty‐nine dogs and 32 cats with pleural cytology and/or histopathology were categorized into malignant pleural disease (15 dogs and 11 cats), pyothorax (34 dogs and 7 cats), chylothorax (20 dogs and 11 cats), transudative (11 dogs and 2 cats), and hemorrhagic effusion (9 dogs and 1 cat). Multivariable logistic regression analysis comparing malignancy to other effusions found that older patient age (dogs: odds ratio 1.28, P = 0.015; cats: odds ratio 1.53, P = 0.005), nodular diaphragmatic pleural thickening (dogs: odds ratio 7.64, P = 0.021; cats: odds ratio 13.67, P = 0.031), costal pleural masses (dogs: odds ratio 21.50, P = 0.018; cats: odds ratio 32.74, P = 0.019), and pulmonary masses (dogs: odds ratio 44.67, P = 0.002; cats: odds ratio 18.26, P = 0.077) were associated with malignancy. In dogs, any costal pleural abnormality (odds ratio 47.55, P = 0.002) and pulmonary masses (odds ratio 10.05, P = 0.004) were associated with malignancy/pyothorax, whereas any costal pleural abnormality (odds ratio 0.14, P = 0.006) and sternal lymphadenopathy (odds ratio 0.22, P = 0.040) were inversely associated with transudates. There were, however, many overlapping abnormalities between effusion types, so further diagnostic testing remains important for diagnosis.